2009
DOI: 10.1007/s12529-009-9052-6
|View full text |Cite
|
Sign up to set email alerts
|

Patient Attitudinal and Behavioral Factors Associated with Warfarin Non-adherence at Outpatient Anticoagulation Clinics

Abstract: Background Warfarin is an anticoagulant effective in preventing stroke, but it has a narrow therapeutic range requiring optimal adherence to achieve the most favorable effects. Purpose The goal of this study was to examine specific patient factors that might help explain warfarin non-adherence at outpatient anticoagulation clinics. Method In a prospective cohort study of 156 adults, we utilized logistic regression analyses to examine the relationship between the five Treatment Prognostics scales from the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
50
0
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 56 publications
1
50
0
8
Order By: Relevance
“…29 Social isolation was strongly associated with noncomprehension of the exercise instructions in this study, adding to prior reports of social isolation as a predictor of non-compliance. [30][31][32] Cognition and high school education were not associated with non-comprehension in any domain of the discharge instructions, although health literacy has been previously identified as a barrier to comprehension. 1,2,6,8 Factors associated with non-comprehension may help identify patients at greater risk, but do not provide a rationale for non-comprehension.…”
Section: Discussionmentioning
confidence: 77%
“…29 Social isolation was strongly associated with noncomprehension of the exercise instructions in this study, adding to prior reports of social isolation as a predictor of non-compliance. [30][31][32] Cognition and high school education were not associated with non-comprehension in any domain of the discharge instructions, although health literacy has been previously identified as a barrier to comprehension. 1,2,6,8 Factors associated with non-comprehension may help identify patients at greater risk, but do not provide a rationale for non-comprehension.…”
Section: Discussionmentioning
confidence: 77%
“…These factors are linked to difficulty maintaining the optimal INR in some patients and result in both nonadherence and discontinuation of warfarin use. 1,2,4,[18][19][20][21][22][23][24] Although the 2-year persistence on warfarin in the Randomized Evaluation of Long-Term Anticoagulant Therapy (RE-LY) trial was ≈83%, 4,25 real-world studies find 1-year persistence rates ranging from 65% to 74%. 1,4,18,20,21,23,24 Young age and lower stroke risk, as calculated using the CHADS 2 score, have been shown to be the primary factors significantly associated with warfarin discontinuation.…”
mentioning
confidence: 99%
“…In the Euro Heart Survey, only about 35% of patients remained on VKAs for 5 years. 26 Cruess and others 27 sought to explain the association between attitudinal and behavioural factors related to nonadherence to warfarin medication regimens. A number of treatment prognostic scales (Interventional Fragility, Medication Abuse, Information Discomfort, and Utilization Excess), as well as social isolation, were associated with warfarin nonadherence.…”
Section: Discussionmentioning
confidence: 99%
“…Patients acknowledging a greater sensitivity to illness-related information from physicians and lack of receptivity to details regarding their medical illness seemed to be at greater risk for warfarin nonadherence. 27 Physicians indicated that concomitant disease, poor INR control, and frequency of monitoring were concerns causing them to classify VKR therapy as difficult to manage. Surprisingly, though, the mean time within the therapeutic range in this cohort (56.4%, albeit with a wide standard deviation [26.9%]) was as good as or better than what the literature suggests is generally obtained.…”
Section: Discussionmentioning
confidence: 99%